NILAI-NILAI DAN TRADISI SEBAGAI PEREKAT: STUDI SOSIOLOGIS PADA KOMUNITAS SUNNI-SYI’AH DI JEPARA - Aksa, Ahmad Habiburrohman (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2024)
This research aims to reveal the values and traditions that exist in the Sunni-Shiite community in building multiculturalism in a pluralistic society. So far, Sunni-Shia relations have been depicted in a conflictual scheme. This research uses qualitative methods from a sociological perspective. The data obtained through in-depth interviews, participatory observation and documentation techniques, this study shows that the atmosphere of peace between Sunni-Shia in Banjaran is reflected in humanitarian social work, social organizations and institutions, organizations and educational institutions. Traditions that develop in the community and values as a belief in the conduct of life every day cannot be negated in its role in building patterns, values that build awareness of multiculturalism so that from that awareness comes tolerance between religious communities.